Phyllanthus emblica aqueous extract retards hepatic steatosis and fibrosis in NAFLD mice in association with the reshaping of intestinal microecology - Luo, Xiaomin; Zhang, Boyu; Pan, Yehua; Gu, Jian; Tan, Rui; Gong, Puyang (Frontiers in Pharmacology, 2022)
Accumulating evidence suggests that dysregulation of the intestinal flora potentially contributes to the occurrence and development of nonalcoholic fatty liver disease (NAFLD). Phyllanthus emblica (PE), an edible and medicinal natural resource, exerts excellent effects on ameliorating NAFLD, but the potential mechanism remains unclear. In the present study, a mouse NAFLD model was established by administering a choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD). The protective effects of the aqueous extract of PE (AEPE) on the gut microbiota and fecal metabolites in NAFLD mice were detected by performing 16S rRNA gene sequencing and untargeted metabolomics. The administration of middle- and high-dose AEPE decreased the levels of ALT, AST, LDL-C, TG, and Hyp and increased HDL-C levels in CDAHFD-fed mice. Hematoxylin-eosin (H&E), Oil Red O and Masson’s trichrome staining indicated that AEPE treatment attenuated hepatic steatosis and fibrotic lesions. Moreover, the disordered intestinal microflora was remodeled by AEPE, including decreases in the abundance of Peptostreptococcaceae, Faecalibaculum and Romboutsia. The untargeted metabolomics analysis showed that AEPE restored the disturbed glutathione metabolism, tryptophan metabolism, taurine and hypotaurine metabolism, and primary bile acid biosynthesis of the gut bacterial community in NAFLD mice, which strongly correlated with hepatic steatosis and fibrosis. Collectively, AEPE potentially ameliorates NAFLD induced by a CDAHFD through a mechanism associated with its modulatory effects on the gut microbiota and microbial metabolism.